HOT BATH THERAPY FOR POSTPARTUM MOTHERS: THE ETHNOCARING PRACTICE IN THE MUNA TRIBE, SOUTHEAST SULAWESI, INDONESIA - Indriastuti, Diah; Tahiruddin, Tahiruddin (Public Health of Indonesia, 2019)
Background: Postpartum mothers are vulnerable to postpartum fatigue, delivery process fatigue, and role transition. The unknown fatigue can trigger stress and anxiety that will lead to postpartum blues and postpartum depression. The ethnocaring of the Muna tribe has a series of care that can prevent postpartum fatigue, including a hot bath.  Objective: To explore the ethnocaring practice on the postpartum care method in the Muna tribe using hot bath and analyze it scientifically. Methods: This study was a qualitative study with an ethnographic approach. The participants were 15 Muna's indigenous midwives and 4 Muna's mothers. Snowball sampling was employed to select the samples. The data were collected through in-depth interviews, focus group discussion and participatory observation. The data validity was made by completing the trustworthiness criteria process.Results: The results of the study were described into 3 themes, namely equipment, treatment, and prohibition. The equipment theme describes tools and materials. Conclusion: The ethnocaring therapy of a hot bath in Muna's postpartum mothers has healthy benefits namely for relaxation, increasing the oxygen uptake, increasing concentration and revitalizing the reproductive organs.